Delimitação da área de influência direta de hipermercado utilizando diferentes modais : o caso do Carrefour Vitória - Tavares, Jonivane (2011)
The methods of area delimitation affected by Poles Generators of Travels (PGT) are generally concerned to shopping centers, whose customers access the pole by car. This work, in turn, aims to adapt one of these methodologies to the supermarket sector, considering different modes of transport. Correa´s (1998) methodology was adjusted to a case study in the Carrefour hypermarket Vitoria. The data used was obtained through interviews to the hypermarket customers, and complemented by the origin and destination data held in 2009 in the Metropolitan Region of Great Vitoria (GVMR), Espirito Santo. The Geographic Informations System ArcGIS 9.3 was used to determine the areas of influence of the hypermarket for customers using car, bus or accessing the pole by foot. The results obtained using the adapted methodology show that the percentage of customers inside the limits of the area of influence of the hypermarket was satisfactory, since it embraces a number of customers higher than the results obtained by Correa´s (1998) methodology. As regards the customer´s characteristics, women are predominant among the clients, they access the pole on foot or by bus, while men mainly use the car. A high amount of customers come from the South and West neighborhoods. In the determination of the areas of influence of the hypermarket, linear regression results showed that the time variable spent by the clients between their origin and the pole is more significant than the distance. The adapted methodology is likely to suit other studies with data availability limitations.